Policies for mandatory public education management in Uruguay - Adriana Aristimuño; Pablo Landoni-Couture; María Inés Vázquez (Arizona State University, 2020)
The purpose of this paper is to analyze the management of public education policies in Uruguay, taking as a reference time frame, two relevant milestones: (i) the period 1995-2004, which we will call "Rama Reform," and (ii) the period 2005-2018, which we will call "FA Administration". To analyze both periods we have used a model developed by Joan Subirats, which defines a series of moments in the public policy cycles,which in this case, we will associate with the educational ones. From this perspective, public policies are considered a "continuous flow of decisions and procedures that are intended to make sense" (Subirats et al., 2012, p. 33). This perspective allows us to establish some common parameters from which to analyze two different historical moments: identify the hierarchical issues as "relevant" or "problematic" that require solution; place the place that these issues took on the national public agenda; analyze the formulation and management of programs that emerged, and identify the evaluation proposals that were defined and implemented to monitor and evaluate their impact. This model addressed substantial issues on the educational agenda within the mandatory range. For their implementation, all the analyzed innovative components required  the revision of current regulations and the strengthening of management. This study identifies articulation and disruption processes that were generated between both cycles, as a way of analyzing local capacities to produce synergies between the different innovative processes implemented during the last decades.